Qatar genome: Insights on genomics from the Middle East. Issue 4 (20th February 2022) - Mbarek, Hamdi; Devadoss Gandhi, Geethanjali; Selvaraj, Senthil; Al‐Muftah, Wadha; Badji, Radja; Al‐Sarraj, Yasser; Saad, Chadi; Darwish, Dima; Alvi, Muhammad; Fadl, Tasnim; Yasin, Heba; Alkuwari, Fatima; et al.
Abstract: Despite recent biomedical breakthroughs and large genomic studies growing momentum, the Middle Eastern population, home to over 400 million people, is underrepresented in the human genome variation databases. Here we describe insights from Phase 1 of the Qatar Genome Program with whole genome sequenced 6047 individuals from Qatar. We identified more than 88 million variants of which 24 million are novel and 23 million are singletons. Consistent with the high consanguinity and founder effects in the region, we found that several rare deleterious variants were more common in the Qatari population while others seem to provide protection against diseases and have shaped the genetic architecture of adaptive phenotypes. These results highlight the value of our data as a resource to advance genetic studies in the Arab and neighboring Middle Eastern populations and will significantly boost the current efforts to improve our understanding of global patterns of human variations, human history, and genetic contributions to health and diseases in diverse populations. Abstract :